The effect of combining PD-1 agonist and low-dose Interleukin-2 on treating systemic lupus erythematosus - Wang, Bing; Chen, Can; Liu, Xia; Zhou, Shuang; Xu, Ting; Wu, Min (Frontiers in Immunology, 2023)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease involving multiple organs. It is often called "immortal cancer" due to the difficulties in disease treatment. As the cornerstone of immune regulation, the programmed cell death protein 1 (PD-1) has been extensively studied in the context of chronic inflammation due to its ability of regulating immune response and immunosuppression (1). Recently, more and more studies on rheumatic immune related complications have also focused on PD-1 and proposed that the use of PD-1 agonist could inhibit the activation of lymphocytes and alleviate SLE disease activity. In this review, we summarized the role of PD-1 in SLE, implicating its potential application as a biomarker to predict SLE disease activity; we also proposed that the combination of PD-1 agonist and low-dose IL-2 may have better therapeutic efficacy, shining light on a new direction for developing specific treatment approaches.